Social deprivation increases cardiac hospitalisations in chronic heart failure independent of disease severity and diuretic non-adherence. Issue 1 (1st January 2000) - Struthers, A D; Anderson, G; Donnan, P T; MacDonald, T
Abstract : OBJECTIVE: To examine whether social deprivation has any independent effect on emergency cardiac hospitalisations in patients with chronic heart failure (CHF). DESIGN: Cohort study of 478 patients with CHF who had been hospitalised before 1993 and who were followed up during 1993 and 1994. SETTING: Emergency admissions within Tayside acute hospitals. PATIENTS: 478 CHF patients who had a previous myocardial infarction, a previous CHF admission, and were on diuretic treatment. MAIN OUTCOME MEASURES: Emergency hospital admissions are divided into those for all causes and those for cardiac causes only. RESULTS: Social deprivation was significantly associated with an increase in the number of cardiac hospitalisations (p = 0.007). This effect was mainly caused by increasing the proportion of patients hospitalised in each deprivation category (26% in deprivation category 1–2 versus 40% in deprivation category 5–6, p = 0.03). This effect of deprivation was independent of disease severity, as judged by the dose of prescribed diuretic, the death rate, and the duration of each hospital stay. Non-adherence with diuretic treatment could not account for these findings either. CONCLUSIONS: Social deprivation increases the chance of a CHF patient being rehospitalised independently of disease severity. Possible explanations are that doctors who look after socially deprived patients have a lower threshold for cardiac hospitalisation of their patients, or that social deprivation alters the way a CHF patient accesses medical care during decompensation. Understanding how social deprivation influences both doctor and patient behaviour in the prehospital phase is now crucial in order to reduce the amplifying effect that social deprivation appears to have on cardiac hospitalisations.